Teaching perfection of professors graduated from the health technological training - José Antúnez Coca; Yaima Rosa Martínez Lambert; Vivian Benito Valenciano (Centro Provincial de Información de Ciencias Médicas, 2017)
Professors preparation is a continuous and systematic work in the higher education. This comprises didactic and pedagogic aspects in the teaching educational process as a way to reach a comprehensive training of the students. In that sense, a pedagogy course  with 7 professors as lecturers was designed, graduated from  the health technological training, and the results of the preparation  process of these professionals are exposed.